EP689 Cytoreduction and hyperthermic intraperitoneal chemotherapy followed by hyperthermic intraperitoneal chemotherapy (CRS+HIPEC) in advanced peritoneal carcinomatous (APC) at the american university of beirut medical center (AUBMC) experience 2007–2018: a retrospective review. (1st November 2019) - Abdallah, R; Seoud, M; El Housheimi, A; Shamseddine, A; Khalifeh, M; Jaafar, I; Jamali, F
Abstract : Introduction/Background: Peritoneal carcinomatosis (PC) has been traditionally considered a terminal disease with median survivals reported in literature of 6–12 months. Cytoreductive surgery (CRS) & hyperthermic intra-peritoneal chemo-therapy (HIPEC) have gradually gained acceptance as standard of care to manage selected PC cases. Our objective is to review the outcome of patients with APC who underwent CRS+HIPEC by the HIPEC team at the AUBMC Methodology: All patients with APC were evaluated by the HIPEC team for eligibility and the majority had either gastrointestinal or gynecological malignancies. We retrospective reviewed data related to their demographics/tumor origin/surgical completeness/adverse events/outcome Results: Since 2007, 53 patients (45% were females) were had CRS and HIPEC. 20 (37.6%) had Pseudomyxoma peritonei (PMP), 12 (23%) ovarian cancer, 14 (26.4%) colorectal cancer, 4 (7.5%) had gastric cancer, 2 (3.7%) had Mesothelioma and one (1.8%) Desmoplastic round cell tumor. Operative and Postoperative demographics and survivals are shown in tables 1 and 2. Median progression free (PFS) and overall survival (OS) are expressed in months. Conclusion: We report the successful establishment of an active peritoneal surface malignancy multidisciplinary treatment program with results comparable to other centers. Careful patient selection, a multidisciplinary approach and proper surgical training and technique are essential for the success of such a program. Disclosure: Nothing to disclose.